Homocystinuria presents with generalized tonic-clonic seizure and Broca’s aphasia - Vivek R. Chaudhari, Dr.; Jigar Mankad, Dr.; Janki Lavingia, Dr.; Manisha Panchal, Dr. (International Journal of Medicine, 2022)
Homocystinuria follows an autosomal recessive pattern and transpires due to Cystathionine beta-synthase enzyme deficiency. This condition is associated with thrombotic and thromboembolic complications due to an increase in homocysteine and methionine levels in the plasma and urine. We present a case of an Indian adolescent boy who presented to us with generalized tonic clinic seizure and Broca's aphasia he was diagnosed as having homocystinuria type 1, and he responded well to treatment.Background: Stroke and seizure disorders in young adults have increased substantially and are a relatively common disorder that presents in the emergency department in all age groups. Secondary seizures are more common and manifest as a result of another underlying pathology. This case demonstrates the importance of considering rarer causes of thrombosis such as arterial thrombosis, even in younger patients, with no obvious risk factors or comorbidities. A detailed medical history and thorough investigations need to be taken to identify a potentially treatable underlying cause.Objective: To increase awareness about this rare etiology and help clinicians to have a higher level of suspicion to diagnose this condition and prevent future life-threatening complications in younger patients with thrombotic and thromboembolic events.Â Â Â